Sistema de recomendaciones para entornos de Digital Signage soportado en un esquema de cooperación smart tv–smartphone (2014)
Advertisement in Digital Signage environments demands the enrichment of the classic approach of recommendation focused on individuals by means of the delivery of ads for a group of people observing a public screen. Even though the accuracy that can be achieved in the recommendations is important, the degree of novelty perceived by the users is even more important. This balance can be obtained not only through the improvement of the recommendation algorithms, but also through an adequate multiscreen cooperation scheme. Therefore, this paper proposes an approach for the construction of a recommendations system for Digital Signage environments based on a Smart TV-Smartphone cooperation scheme.